Microplastics: Notes on Recycling, Waste, and Environmental Prevalence - Liu, David (International Journal of Scientific Research and Management (IJSRM), 2025)
Microplastics (MPs), industrial byproduct plastic particles less than 5 mm in size [1], have emerged as pervasive environmental pollutants, posing health risks to biological ecosystems through a variety of mechanisms. These mechanisms include uptake pathways in plants, whose contamination affects their physiological processes. While their unapparent size and ubiquitous nature can make microplastics an easy subject to overlook, the long-term potential harm of microplastics on our environment warrants attention. Currently, approximately 40% of single-use plastics are discarded into land and waterways, whose active processes can further degrade them into micro- and nano-size particles [2]. These microplastics can carry hazardous chemicals that can cause serious health risks such as human cell injury, hormone disruption, and cardiovascular disease. Colloquially known as ‘microplastics’, these debris are highly permeative and traverse through the environment with ease, eventually impacting plant physiology. Through ingestion, their introduction into the bodies of animals, including humans, has also been known to cause cytotoxicity, unnoticed inflammation responses, hormonal disruptions, and more [3]. The resulting damages have included acute organ disease and general disorder of biochemical constitution. Thus, it is critical to analyze the mechanisms of soil, water, and air dispersal of microplastics and their corresponding assimilation into plants. By studying these mechanics of plant permeation, it becomes possible to devise strategies to eliminate their detriments to the environment and health.